The Pointe of the Pen : Nineteenth-Century Poetry and the Balletic Imagination - Tontiplaphol, Betsy Winakur (Romantic Reconfigurations Studies in Literature and Culture 1780 1850 Ser., 2021)
The Pointe of the Pen argues that the nineteenth century's balletic innovations the most iconic of which was the ballerina en pointe, or dancing on the tips of her toes - assisted nineteenth-century poets in both conceiving and articulating the object of verse in an age increasingly shaped by the novel.